Lysimachia xuyongensis (Primulaceae), a new species from Sichuan, China - Ju, Wen-Bin; Deng, Heng-Ning; Xu, Bo; He, Xing-Jin; Gao, Xin-Fen (Phytotaxa, 2021)
A new species, Lysimachia xuyongensis X.F.Gao & W.B.Ju, from China is described and illustrated. The new species morphologically resembles L. miyiensis, L. paridiformis var. stenophylla and L. phyllocephala var. polycephala, but it clearly differs by having stems prostrate at base, dense white multicellular hairs, leave 4, lower scalelike, leaf blades and calyx carrying sparsely reddish glandular punctation, pedicel less than 5 mm, corolla lobes without glandular and ovary glabrous.